Pelaksanaan Jual Beli Perkebunan Sengon dengan Akad Ijarah Menurut Hukum Ekonomi Syariah - Baidah, Zu; Swadjaja, Isma (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
This research discusses about the practice of buying and selling sengon plantations with lease agreements carried out by communities in the village of Denok, Lumajang district, Lumajang district. The practice of buying and selling does not appear to be in line with the transaction concepts regulated in Sharia Economic Law. Therefore the author feels interested in the importance of further examining this issue from the perspective of Sharia Economic Law, specifically by using the theory of buying and selling (bai') and rent (ijarah). This research is limited to the following issues: (1) How is the sale and purchase of sengon plantations with ijarah contracts carried out by the people in Denok village, Lumajang district, Lumajang district? (2) What is the implementation of the sale and purchase of sengon plantation with ijarah contract by the people in the village of Denok Lumajang sub-district Lumajang regency according to Sharia Economic Law? And (3) What is the implementation of the sale and purchase of sengon plantations with ijarah contracts by people in the village of Denok Lumajang sub-district Lumajang district according to the principles of Sharia Economic Law? This research is field research where research is conducted by approaching the subject and object of research in the research location. The approach that the author chose in this study is a case study approach, which is an approach used in studies of certain cases from various legal aspects. Data collection techniques that will be selected to obtain accurate data in this study are documentation, observation, and interviews.The results of this research are: (1) The implementation of the buying and selling of sengon plantations with the ijarah contract can be explained by the following points: (a) The type of contract that is said is a lease agreement, although in the contract there are two legal actions, namely buying and selling sengon trees and rental of plantation land (b) Regarding the object of the contract there are two, namely sengon trees and plantation land. For the contract object in the form of sengon tree ownership, the owner moves from the owner to the tenant, while for the contract object in the form of sengon tree does not take ownership, only the right to use temporarily from the owner to the tenant within a specified and agreed period. (c) As a legal consequence of the lease agreement, the owner of the plantation gets an amount of money from the lessee, and the tenant gets a number of sengon plants to be owned (being the owner of sengon) and the right to use the land for the specified time. (2) The sale and purchase of sengon plantations with the ijarah contract in Denok village Lumajang sub-district Lumajang district is in accordance with the theory of akad, bai â€™(buying and selling), and ijarah (rent) in Sharia Economic Law. (3) The sale and purchase of sengon plantations with the ijarah contract in Denok village Lumajang sub-district Lumajang district is in accordance with the principles of Sharia Economic Law which includes the principle of permissibility, the principle of benefit, the principle of willingness, the principle of justice, and customary principles as law.Â Keywords: Sengon, Transaction, Ijarah, Sharia Economic Law.